Evaluation of electric field for electrode of a pulse electroacoustic (PEA) equipment - Nurasilah, Khamar Ludin (2022)
The usage of electricity had shown a higher number of increments nowadays. It is due to a higher number of users requesting an improvement of power system equipment with a high level of reliability and safety. The power system grid connects the power plants through the high voltage transmission lines and distribution lines to the consumers. The high voltage direct current (HVDC) transmission line is usually used to transfer the power being generated to the load area. HVDC transmission shows lower losses, low cost, easy to control and adjust compared to the high voltage alternating current (HVAC) transmission. In the HVDC transmission line, the polyethylene (PE) power cable has been widely used as electrical insulation for power cables due to its electrical and mechanical properties. In the last two decades, a significant effort has been made to understand better the internal charge distribution inside dielectric materials. There are two types of methods being used which were destructive and non-destructive methods. However, the development of the non-destructive method has a better result which gives details about charge distribution inside a dielectric material. Low-Density Polyethylene was used during this study as sample selected due to its characters with a density range between 0.910 – 0.925 g/cm3, weaker intermolecular forces, lower tensile strength, higher ductility and can be produced under high pressure. However, it also has excellent properties such as low dielectric loss, high dielectric strength, chemical inertness, low moisture uptake and ease of extrusion, making it easy to use in many kinds of power applications. In this study, the effect of an electric field with different edge electrodes on dielectric material was being observed and analyzed using the Finite Element Method (FEM). Based on the results, we can see that the electric field is higher at dielectric insulating materials when the radius(r) approaches 0mm due to the sharp edge of the electrode. As the radius of the electrode edge increases, the electric field decreases. It proves that the edge of an electrode has an effect on the electric field in a dielectric material. The electric field additionally diminishes as the gap between electrodes increases. The presence of epoxy during the simulation didn’t give a high impact on the electric field distribution but it needed to improve the insulation and prevent the discharge between the electrodes. In this examination, the field calculations were done utilizing the FEM.